ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING SAHAM PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - FENDY W., YOGI (Jurnal Akuntansi AKUNESA, 2014)
The Bidding process of the company stock to the public for the first time through the stock exchange is called initial public offering (IPO). Underpricing phenomenon occurs during IPO process, when stock price on the primary market is cheaper than the stock price on secondary market. This study aims to examine to the effect of current ratio, age, size, ROA, EPS from the company and financial leverage toward the underpricing rate of non financial  company stocks listed in Indonesian Stock Exchange. The study  use multiple regression to test the partial and simultan effect. The sample (are) used in this study. It all the company was registered in BEI during 2008-2012. Sample were obtained with purposive sampling method on 50 company. Keywords : underpricing, IPO